E-business process management technologies and solutions - Sounderpandian, Jayavel; Sinha, Tapen; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This book explores the issues of supply chain management with new perspective providing examples of integrated framework for global SCM, novel ways of improving flexibility, responsiveness, and competitiveness via strategic IT alliances among channel members in a supply chain network, and techniques that might facilitate improved strategic decision making in a SCM environment"--Provided by publisher.
E-Governance -- Introduction to Cryptography -- E-Business Process Management and Intellectual Property: Issues and Implications -- E-Business Technologies in E-Market Literature -- E-Commerce Standards: Transforming Industry Practice -- Interoperability on the Road to Enhance Government-to-Business -- A Brief Overview of Wireless Systems and Standards -- Wireless Networks Based on WiFi and Related Technologies -- Consumers' Preferences and Attitudes Toward Mobile Office Use: A Technology Trade-Off Research Agenda -- Global Outsourcing of Business Services -- Sourcing and Outsourcing Arithmetic -- Strategies for Business Process Outsourcing: An Analysis of Alternatives, Opportunities, and Risks -- Developing and Delivering Online Courses -- The Business of Online Education -- Risk Management -- E-Business Risk Management in Firms -- Electronic Risk Management.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 22, 2010).
Keywords: Electronic commerce -- Management; Electronic books